Child Sexual Abuse Risk Factors, Outcomes, and Protective Factors in India: A Conceptual and framework model. - Dr. Priyanka Sharma; Dr. Amit Kumar (Innovative Research Thoughts, 2023)
Until recently, academic research in India was primarily concerned with crimes against females of reproductive age, such as rape or sex trafficking, while downplaying sexual abuse of pre-pubertal or adolescent boys and girls. However, in recent years, child sexual abuse has been recognised and reported as a criminal justice issue, with an increasing number of such incidents being published in the country. This article proposes a conceptual framework delineating the risk factors, outcomes, and protective factors of child sexual abuse in India based on a systematic review of the existing literature. The paper concludes with policy and research implications.